Journal Proceedings on applied botany, genetics and breeding: to the 110 th anniversary of the foundation - E. A. Sokolova; I. V. Kotelkina (Труды по прикладной ботанике, генетике и селекции)
The landmarks of the age-long history of the scientific journal Proceedings on Applied Botany, Genetics and Breeding are briefly presented. Its first issue was published in 1908. Practically, its publication has never been interrupted for the past 100 years. The journal has reflected the establishment and development of VIR from its first years of existence as the Bureau of Applied Botany. Its main editors, authors and reviewers were outstanding scientists in the sphere of biological and agricultural sciences as well as other researchers whose works have enriched the domestic and worldwide science.